2006
DOI: 10.1088/0957-0233/17/8/005
|View full text |Cite
|
Sign up to set email alerts
|

Real time three-dimensional electrical impedance tomography applied in multiphase flow imaging

Abstract: In many industrial applications the aim is to obtain information on three-dimensional (3D) material distribution within the process vessels. With standard two-dimensional (2D) techniques only vague cross-sectional information can be obtained. It could be possible to carry out several 2D reconstructions on different layers and in this way to obtain 3D information. However, in this approach errors are induced since no real 3D information is utilized in the image reconstruction. In this paper we describe an appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 6 publications
0
28
0
1
Order By: Relevance
“…In medicine, it has been used for gastric emptying and pH measurements [20], cancer detection [21] and tissue characterization [22]. In industry, it has been used for the nondestructive testing of polycrystalline diamond [23], 3D malformations detection in industrial pressure filtration systems [24]. In geophysics, it has been used for measuring the polarization properties of soils and sediments [25] and the analysis of gravel-air-seawater mixture [26].…”
Section: A Electrical Impedance Tomographymentioning
confidence: 99%
“…In medicine, it has been used for gastric emptying and pH measurements [20], cancer detection [21] and tissue characterization [22]. In industry, it has been used for the nondestructive testing of polycrystalline diamond [23], 3D malformations detection in industrial pressure filtration systems [24]. In geophysics, it has been used for measuring the polarization properties of soils and sediments [25] and the analysis of gravel-air-seawater mixture [26].…”
Section: A Electrical Impedance Tomographymentioning
confidence: 99%
“…There has not been a significant volume of research done on multi-planar strategies to date. Some exceptions include [2], who reported that resolution between planes improved when current injection and voltage measurement are taken between horizontally and vertically adjacent electrodes, and [3] applied cross-planar current drives for 3D imaging. [4] claimed that there were negligible differences between a reconstruction using a planar and a non-planar adjacent measurement strategy.…”
Section: Obtaining More Information Through Measurement Strategiesmentioning
confidence: 99%
“…Current-injecting electrodes were always on electrode layers 1 and 3, or on 2 and 4. Similar current injections were used as in laboratory measurements described in [23], in order to generate rather uniform current densities in the middle region of the pipe segment. Voltages were measured between 64 electrode pairs.…”
Section: Forward Problemmentioning
confidence: 99%